Peran digitalisasi dalam meningkatkan efektivitas manajemen risiko lembaga keuangan syariah - hidayatullah, Moh. bayu (Maliki Interdisciplinary Journal, 2025)
Digitalization has become a crucial pillar in enhancing the effectiveness of risk management within Islamic financial institutions. Through the application of technologies such as Artificial Intelligence (AI), big data, and blockchain, the processes of risk identification, analysis, mitigation, and monitoring can be carried out automatically and in real time. These innovations not only improve operational efficiency and decision-making accuracy but also strengthen transparency and compliance with Sharia principles that prohibit riba (usury), gharar (uncertainty), and maysir (gambling). Literature reviews and case studies from Bank Syariah Indonesia (BSI) indicate that the integration of digitalization with Sharia governance enhances financial stability, customer trust, and promotes equitable financial inclusion. Nevertheless, digital transformation faces several challenges, including regulatory readiness, cybersecurity, and public digital literacy. Therefore, strategic collaboration among regulators, academics, and Sharia scholars is essential to ensure that the digitalization process remains aligned with Islamic values while effectively addressing the demands of the Fourth Industrial Revolution era.